2019
DOI: 10.22146/ijc.40910
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Methylene Blue from Aqueous Solution by Using Electrical Arc Furnace (EAF) Slag

Abstract: In recent years, environmental protection has gained a major concern. In line with the rapid growth of various industries, high amount of effluent has been generated and discharged to the environment. One of the concerns is the presence of synthetic dye in the wastewater stream, as it may endanger human and aquatic life. In this experiment, the Electrical Arc Furnace (EAF) slag has been used as an adsorbent to remove methylene blue from the aqueous solution. Batch experiments have been conducted, and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The maximum adsorption capacity for treated EAF slag was 14.2029 mg/g, and raw EAF slag was 9.615 mg/g. The maximum removal percentage for treated EAF Slag was 71.01%, whereas raw EAF showed 37.19% removal at pH 10 [48]. In another study, Omale et al (2019) investigated Malaysian EAF slag utilization for effective application in direct aqueous sequestration of carbon dioxide under ambient temperature and concluded that the maximum CO 2 uptake capacity was 5.836 wt%, resulting in sequestration of 58.36 g CO 2 /kg of steel slag and the sequestration efficiency of 32.53% [30].…”
Section: Filter or Adsorbent In Wastewater Treatment Plantmentioning
confidence: 91%
See 2 more Smart Citations
“…The maximum adsorption capacity for treated EAF slag was 14.2029 mg/g, and raw EAF slag was 9.615 mg/g. The maximum removal percentage for treated EAF Slag was 71.01%, whereas raw EAF showed 37.19% removal at pH 10 [48]. In another study, Omale et al (2019) investigated Malaysian EAF slag utilization for effective application in direct aqueous sequestration of carbon dioxide under ambient temperature and concluded that the maximum CO 2 uptake capacity was 5.836 wt%, resulting in sequestration of 58.36 g CO 2 /kg of steel slag and the sequestration efficiency of 32.53% [30].…”
Section: Filter or Adsorbent In Wastewater Treatment Plantmentioning
confidence: 91%
“…Thus, Malaysia needs to make recycling beneficial to both manufacturers and the environment. Initiatives may be taken toward a better Malaysia [22,29,30,34,43,[46][47][48].…”
Section: Solid Wastes and By-products Issues In The Steelmaking Industrymentioning
confidence: 99%
See 1 more Smart Citation